Moral psychology and genetic engineering - Kaebnick, Gregory E. (The Hastings Center report, 2016)
For the last six months or so, some of us at The Hastings Center have been participating in a kind of short-term book group. Together we have been thinking about the contribution of moral psychology to bioethics. One of our questions is whether bioethics’ understanding of moral values should draw on what moral psychology tells us about moral values. Bioethics tends to look to philosophy for guidance. Can it learn from insights in moral psychology into the biological, environmental, and cultural influences on morality? The question can be taken in many directions. One that I've wrestled with has to do with debates about genetic engineering, where a common concern is that genetic alteration of other organisms, and maybe also of humans, doesn't sit well with the kind of relationship that people want to have to nature.